Antioxidant and Enzyme Inhibitory Potential of Streptomyces sp. G-18 Grown in Various Media - Ashok, G. C.; Prakash Pradhan, Suman; Kumar Karki, Krishna; Khadka, Aakriti; Bhandari, Aishwarya; Prasad Pandey, Bishnu (International Journal of Microbiology, 2023)
Streptomyces are bacteria well known for producing bioactive secondary metabolites which are commonly found in diverse habitats. The biosynthesis of metabolites from Streptomyces is influenced by various factors such as the growth medium, environmental conditions, and gene regulation. This study aimed to investigate the influence of different growth media on biomass production and the antioxidant and enzyme inhibitory potential of a crude extract obtained from Streptomyces sp. G-18 isolated from high altitudinal soil of Nepal. The highest dry weight growth was observed in R2YE medium (184 mg/L), followed by R5 (144 mg/L), YEME (38 mg/L), and R5M media (30 mg/L). The crude extract showed notable antioxidant activities against free radicals. The highest alpha-amylase inhibition was observed in the R2YE medium, and worthy lipase and tyrosinase inhibition was observed in the YEME medium. However, only the R2YE medium exhibited inhibitory potential against elastase and acetylcholinesterase, while crude extracts from R5, YEME, and R5 modified did not show any such activity. Overall, our findings suggest that the production of bioactive secondary metabolites in Streptomyces sp. G-18 was significantly influenced by the growth medium. This strain may be a promising source of enzyme inhibitors with potential applications in the pharmaceutical and cosmetic industries.